“Sardoodledom” on the English Stage: T. W. Robertson and the Assimilation of Well-Made Play into the English Theatre - Prośniak, Anna (Text Matters: A Journal of Literature, Theory and Culture, 2020)
The article discusses a vital figure in the development of modern English theatre, Thomas William Robertson, in the context of his borrowings, inspirations, translations and adaptations of the French dramatic formula pièce bien faite (well-made play). The paper gives the definition and enumerates features of the formula created with great success by the French dramatist Eugène Scribe. Presenting the figure of Thomas William Robertson, the father of theatre management and realism in Victorian theatre, the focus is placed on his adaptations of French plays and his incorporation of the formula of the well-made play and its conventional dramatic devices into his original, and most successful, plays, Society and Caste. The paper also examines the critical response to the well-made play in England and dramatists who use its formula, especially from the point of view of George Bernard Shaw, who famously called the French plays of Scribe and Victorien Sardou—“Sardoodledom.”